2008
DOI: 10.1038/leu.2008.241
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E genotype as a determinant of survival in chronic lymphocytic leukemia

Abstract: Survival of chronic lymphocytic leukemia (CLL) cells requires sustained activation of the antiapoptotic PI-3-K/Akt pathway, and many therapies for CLL cause leukemia cell death by triggering apoptosis. Blood lipoprotein particles are either pro-or antiapoptotic. High-density lipoprotein particles are antiapoptotic through sphingosine-1-phosphate receptor 3-mediated activation of the PI-3-K/Akt pathway. Apolipoprotein E4 (apoE4)-very low density lipoproteins (VLDL) increase apoptosis, but the apoE2-VLDL and apo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Recently, it was reported that female CLL patients, who exhibit a apolipoprotein E4 (apoE4) genotype, have longer survival rates than non-apoE4 patients. 68 ApoE4 is the pro-apoptotic isoform of the apoE glycoprotein present in VLDL particles. Furthermore, they confirmed previous findings that poor-outcome CLL patients express higher levels of lipoprotein lipase mRNAFtranscript of the enzyme responsible for converting VLDL to LDL.…”
Section: Classification Methodsmentioning
confidence: 99%
“…Recently, it was reported that female CLL patients, who exhibit a apolipoprotein E4 (apoE4) genotype, have longer survival rates than non-apoE4 patients. 68 ApoE4 is the pro-apoptotic isoform of the apoE glycoprotein present in VLDL particles. Furthermore, they confirmed previous findings that poor-outcome CLL patients express higher levels of lipoprotein lipase mRNAFtranscript of the enzyme responsible for converting VLDL to LDL.…”
Section: Classification Methodsmentioning
confidence: 99%
“…15 Finally, we identified several mutations affecting poorly characterized genes (for example, in TMEM56, NGLY1, GPR158, CYB5D2) without any known functions in blood cells, or mutations in genes with well-known functions that are most likely not relevant for hematological malignancy. For example, SEMG2 encodes a seminal protein and CUBN encodes the intrinsic factor, which is secreted by parietal cells in the gastric epithelium.…”
Section: Letters To the Editormentioning
confidence: 99%
“…[3][4][5] This kinase is also activated in response to many other microenvironmental stimuli that increase leukemic cell survival or induce proliferation, including CXCL12, CD40 ligand, IL-4, CpG oligonucleotides, lysophosphatidic acid, high-density lipoprotein particles and contact with bone marrow stromal cells. [6][7][8][9][10][11][12][13] In addition, increased basal Akt activity has been reported in some studies, suggesting that constitutive Akt signaling may contribute to the increased survival of the malignant lymphocytes. In line with this possibility, specific inhibition or downregulation of Akt has been shown to induce apoptosis in freshly isolated CLL cells.…”
Section: Introductionmentioning
confidence: 99%